POTENSI PROBIOTIK DALAM TATALAKSANA ORAL CANDIDIASIS: Ulasan Sistematik - Fitriasari, Nuri; Wahyuni, Indah Suasani (Odonto : Dental Journal, 2021)
Background: Probiotics are living microorganisms which when given in sufficient quantities will provide health benefits to humans. The role of probiotic bacteria in the oral environment is to prevent attachment of pathogenic bacteria, produce antimicrobial substances, activate and regulate the immune response. Today probiotics are recommended for oral health maintenance and management of oral diseases, one of which is Oral Candidiasis. The purpose of this paper is to describe the potential of probiotics in the management of Oral Candidiasis.Method: Systematic literature review used literature search methods in electronic databases: Google Scholar, Science Direct, and PubMed. The keywords were "lactobacillus", "oral candidiasis", and "probiotic". The inclusion criteria for selection of scientific articles were years of publication from 2010 to 2018; in vitro and clinical trials; published in English and full paper available. Out of 86 articles that have been screened, eleven articles have been included in this review.Result: The articles showed the potential use of probiotics in non-clinical trials as well as clinical trial in management of oral candidiasis in various age groups, and supports the treatment with no side effects. Mechanisms of probiotic action are known to have the potential to inhibit and reduce candida spp. in the oral cavity. Conclusion: Probiotics have the potential as antifungal agent in the prevention and therapy of oral candidiasis